Stanniocalcin-1 secreted by human umbilical mesenchymal stem cells regulates interleukin-10 expression via the PI3K/AKT/mTOR pathway in alveolar macrophages. (February 2023) - Xia, Ting-Ting; Hu, Rong; Shao, Cheng-Jie; Feng, Yan; Yang, Xing-Le; Xie, Yong-Peng; Shi, Jia-Xin; Li, Jia-Shu; Li, Xiao-Min
Graphical abstract: Highlights: LPS stimulates HUMSC to secrete high levels of STC-1 and IL-10 when co-cultured with alveolar macrophages. STC-1 knockdown in HUMSC decreased the phosphorylation of PI3K, AKT and mTOR and suppressed IL-10 expression in alveolar macrophages. Abstract: Acute respiratory distress syndrome (ARDS) is a syndrome of acute respiratory failure caused by infection, trauma, shock, aspiration or drug reaction. The pathogenesis of ARDS is characterized as an unregulated inflammatory storm, which causes endothelial and epithelial layer damage, leading to alveolar fluid accumulation and pulmonary edema. Previous studies have shown the potential role of mesenchymal stem cells (MSC) in combating the inflammatory cascade by increasing the anti-inflammatory mediator interleukin-10 (IL-10). However, the involved mechanisms are unclear. Here we investigated whether a key immunomodulatory regulator, stanniocalcin-1 (STC-1), was secreted by MSC to activate phosphoinositide 3-kinase/protein kinase B (PI3K/AKT)/ mammalian target of rapamycin (mTOR) signaling pathway to increase IL-10 expression in alveolar macrophages. Lipopolysaccharide (LPS)-stimulated alveolar macrophages co-cultured with human umbilical mesenchymal stem cells (HUMSC) secreted high levels of IL-10. HUMSC co-cultured with alveolar macrophages expressed high STC-1 levels and increased PI3K, AKT and mTOR phosphorylation after LPS activation in alveolar macrophages. STC-1 knockdown in HUMSC decreased the phosphorylation of PI3K, AKT and mTOR and suppressed IL-10 expression in alveolar macrophages. Rapamycin (an mTOR inhibitor) reduced IL-10 secretion in alveolar macrophages. These results, together with our previous study and others, indicate that the PI3K/AKT/mTOR pathway is involved in the regulation of IL-10 production by STC-1 secreted by HUMSC in alveolar macrophages.